Marrying the elements : the extent of influence of bridal magazines on Singaporean weddings. - Khoe, Katrina. (2013)
This paper explores the extent in which bridal magazines affect the choices made by Singaporean couples in pertaining to the planning and execution of their wedding ceremony. The paper aims to determine the thought process that go behind the choosing of different ‘symbols’ and the meanings associated with such symbols that couples incorporate into their final ceremony. The study will also look at how Singaporean couples are able to create their own unique cultural identity as portrayed in their weddings amidst increasing global influences, blending in traces of tradition with a modern twist. Hints of racial categorization among the results will also be discussed in the paper.